Farmers’ intrinsic motivations, barriers to the adoption of conservation practices and effectiveness of policy instruments: Empirical evidence from northern Australia - Greiner, Romy; Gregg, Daniel (Land use policy, 2011)
The rate and extent of adoption of conservation practices by farmers is influenced, in principle, by characteristics of the practices and those of the farmers. Governments use policy instruments to increase the rate of adoption of practices which generate public benefits if it is deemed that privately optimal adoption rates will not lead to publicly optimal conservation outcomes. Recent nation-wide conservation programs in Australia have attracted criticism for low levels of effectiveness and efficiency. Could it be that program design has ignored key adoption factors, in particular characteristics of the target audience? If adoption is subject to personal factors, such as the motivations for farming, then it is likely that so are farmers’ responses to policy approaches and instruments. In this case study, surveys were conducted of farmers in three regions within the tropical savannas of northern Australia, where land-use systems are characterized by large-scale broad-acre beef grazing enterprises. Inter alia, these surveys collected data on graziers’ motivations, impediments to adoption of conservation practices, and perceived effectiveness of policy instruments in overcoming impediments. The research found that graziers had a very high level of conservation and lifestyle motivation and were motivated to lesser extents by financial/economic and social considerations, pointing to a strong stewardship ethic of graziers, or altruistic motif. Motivational profiles were significantly correlated with farmers’ perceptions about what constrained them from implementing conservation based management systems. Motivational profiles also explained differences in farmers’ perceptions of and stated propensity to interact with policy instruments, particularly at a regional scale and in the context of historical government interventions. On the basis of the empirical evidence presented, governments would be well advised to harness the diverse set of aspirations and motivations of farmers when designing conservation programs rather than. In particular, conservation programs need to take advantage of farmers’ stewardship ethic for maximum effectiveness and efficiency, and minimize the risk of crowding out intrinsic motivation and altruistic behaviours.